The adventures of the wishing-chair - Blyton, Enid. (b, 2013)
When Mollie and Peter go to buy their mother a birthday present, they discover the most extraordinary thing: a chair that can fly and grant wishes! The Wishing-Chair takes them on some marvellous adventures - to a castle where they narrowly escape from a giant and rescue Chinky the pixie, to the Land of Dreams, and to a disappearing island!
Keywords: Children's stories, English